Novel evolutionary lineages in Labeobarbus (Cypriniformes; Cyprinidae) based on phylogenetic analyses of mtDNA sequences - Beshera, Kebede A.; Harris, Phillip M.; Mayden, Richard L. (Zootaxa, 2016)
Phylogenetic relationships within Labeobarbus, the large-sized hexaploid cyprinids, were examined using cytochrome b gene sequences from a broad range of geographic localities and multiple taxa. Maximum likelihood and Bayesian methods revealed novel lineages from previously unsampled drainages in central (Congo River), eastern (Genale River) and southeastern (Revue and Mussapa Grande rivers) Africa. Relationships of some species of Varicorhinus in Africa (excluding ‘V.’ maroccanus) render Labeobarbus as paraphyletic. ‘Varicorhinus’ beso, ‘V.’ jubae, ‘V.’ mariae, ‘V.’ nelspruitensis, and ‘V.’ steindachneri are transferred to Labeobarbus. Bayesian estimation of time to most recent common ancestor suggested that Labeobarbus originated in the Late Miocene while lineage diversification began during the Late Miocene-Early Pliocene and continued to the late Pleistocene. The relationships presented herein provide phylogenetic resolution within Labeobarbus and advances our knowledge of genetic diversity within the lineage as well as provides some interesting insight into the hydrographic and geologic history of Africa.